Literasi Hubb Era Digital - Aimah, Siti; Hidayati, Nur; Imamah, Istianatul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
The current investigation addresses the urgent need for effective counter-narrative strategies against the proliferation of digital extremism. This article analyzes the Hubb Literacy Model implemented by contemporary pesantren as a concrete framework for teaching compassion, tolerance, and religious moderation to safeguard the digital landscape. Utilizing a qualitative case study design, the inquiry involved in-depth interviews with spiritual leaders and students, participant observation, and a comprehensive analysis of curriculum documents at Pesantren Darussalam Blokagung. The findings reveal that the Hubb Literacy Model effectively mitigates extremism through five strategic pillars: the integration of digitalized classical texts (Kitab Kuning), the production of Tawassuṭ (moderate) social media content, the critical filtering of extremist narratives through the Uswah (exemplary) guidance of the Kiai, the institutionalization of Hubb (love) as a daily soft-skill curriculum, and the strengthening of the